Odpowiedzi

Najlepsza Odpowiedź!
2009-11-23T18:43:43+01:00
A) 3(a+b)+(a-2b) = 3a+3b+a-2b = 4a +b
b) -4(x-z)-(x+y) = -4x+4z-x-y = -5x+4z-y
c) 5(4x-7)+(7-4x) = 20x-35+7-4x = 16x -28
d) (4x-y)-2(x+y) = 4x-y-2x-2y = 2x-3y
2009-11-23T18:44:12+01:00
A) 3(a+b)+(a-2b) =
3a + 3b + a - 2b = 4a + b

b) -4(x-z)-(x+y) =
-4x + 4z -x -y = -5x - y +4z

c) 5(4x-7)+(7-4x) =
20x - 35 + 7 - 4x = 16x - 28

d) (4x-y)-2(x+y) =
4x - y - 2x - 2y = 2x - 3y
2009-11-23T19:40:59+01:00
A) 3(a+b)+(a-2b) = 3a+3b+a-2b= 4a+b
b) -4(x-z)-(x+y) = -4x+4z-x-y= -5x+4z-y
c) 5(4x-7)+(7-4x) =20x-35+7-4x=16x-28
d) (4x-y)-2(x+y)=4x-y-2x-2y=2x-3y